SISTEM INFORMASI PENCATATAN HUTANG DALAM PENGADAAN OBAT BERBASIS MULTIUSER: (STUDI KASUS DI RSUD AMBARAWA) - Fransisca Khurnia Erkhani; Indra Ava Dianta (Pusat Riset dan Inovasi Nasional, 2024)
The development of information technology is growing rapidly from day to day. This is supported by the presence of a computer as a data processing media that can assist the process of providing information. Computers are one of the basic needs for an agency or company to assist in recording and processing data in order to produce fast, precise and accurate information. The need for a computer is due to the number of transactions or important data of agencies or companies that are very diverse so that a database is needed that can store and process the data into information quickly, accurately, and can be used whenever needed This information is needed to help a company or agency in making the right decisions for the company's survival in the future. Likewise, the Ambarawa Regional General Hospital (RSUD) uses computers as a medium for recording and processing data to produce information. The Regional General Hospital (RSUD) Ambarawa is one of the institutions belonging to Semarang Regency which is engaged in public health services. Ambarawa Hospital is located at Jalan Kartini No. 101 Ambarawa. The beginning of its establishment was in 1930 in the form of a Private Hospital belonging to the Catholic Foundation and in 1945 the ownership of the Hospital was handed over to the Semarang Regency Government with management still carried out by the Catholic Foundation. Then in 1956 the ownership and management of the Hospital was completely handed over to the Semarang Regency Government. As of 2012, Ambarawa Hospital has been in the form of a Regional Public Service Agency (BLUD).